2018
DOI: 10.3928/02793695-20170929-03
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative Study of Depression Literacy Among Korean American Parents of Adolescents

Abstract: Lack of depression literacy is associated with low help-seeking behaviors for mental health care in adolescents. As parents generally determine adolescents' health care, ensuring parents can recognize depressive symptoms is crucial. The current study explored depression literacy among Korean American parents of adolescents ages 12 to 19 using a qualitative descriptive design. Semantic content analysis was performed using data from three focus group interviews conducted in 2015 with Korean American parents (10 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 16 publications
0
18
0
Order By: Relevance
“…Malaysian caregivers were found to have limited knowledge of mental illness and treatment, associated with religious and spiritual beliefs of unknown and supernatural causes of mental illness (Mohammad et al, 2012). Korean-American parents had limited knowledge and some misconceptions about the causes of depression and its treatment (Jeong, McCreary, & Hughes, 2017). The study also found that Korean fathers had less knowledge about depressive symptoms and treatment than mothers with their primary focus on earning and providing for the household (Jeong et al, 2017).…”
Section: Knowledge and Understandingmentioning
confidence: 94%
See 3 more Smart Citations
“…Malaysian caregivers were found to have limited knowledge of mental illness and treatment, associated with religious and spiritual beliefs of unknown and supernatural causes of mental illness (Mohammad et al, 2012). Korean-American parents had limited knowledge and some misconceptions about the causes of depression and its treatment (Jeong, McCreary, & Hughes, 2017). The study also found that Korean fathers had less knowledge about depressive symptoms and treatment than mothers with their primary focus on earning and providing for the household (Jeong et al, 2017).…”
Section: Knowledge and Understandingmentioning
confidence: 94%
“…In contrast, parents in two other qualitative studies held negative attitudes (e.g. fear, mistrust, lack of faith) to mental health services that was based on observation of others' unsuccessful help-seeking experience (Jeong et al, 2017;Umpierre et al, 2015).…”
Section: Attitudes and Beliefsmentioning
confidence: 98%
See 2 more Smart Citations
“…Depression literacy (D-Lit) is an essential requirement to combat the disorder as it addresses the identification of depressive symptoms, receiving treatment options as well as making critical decisions during emergencies (Jeong et al 2018;Arafat et al 2018a). Moreover, it plays a contributory role in the treatment of depression as it is a chronic disorder (Arafat et al 2018a,b;Arafat et al 2017).…”
Section: Health and Depression Literacymentioning
confidence: 99%